High Performance Flexible Piezoelectric Nanogenerators based on BaTiO3 Nanofibers in Different Alignment Modes - Yan, Jing; Jeong, Young Gyu (ACS applied materials & interfaces, 2016)
Piezoelectric nanogenerators, harvesting energy from mechanical stimuli in our living environments, hold great promise to power sustainable self-sufficient micro/nanosystems and mobile/portable electronics. BaTiO3 as a lead-free material with high piezoelectric coefficient and dielectric constant has been widely examined to realize nanogenerators, capacitors, sensors, etc. In this study, polydimethylsiloxane (PDMS)-based flexible composites including BaTiO3 nanofibers with different alignment modes were manufactured and their piezoelectric performance was examined. For the study, BaTiO3 nanofibers were prepared by an electrospinning technique utilizing a sol-gel precursor and following calcination process, and they were then aligned vertically or horizontally or randomly in PDMS matrix-based nanogenerators. The morphological structures of BaTiO3 nanofibers and their nanogenerators were analyzed by using SEM images. The crystal structures of the nanogenerators before and after poling were characterized by X-ray diffraction. The dielectric and piezoelectric properties of the nanogenerators were investigated as a function of the nanofiber alignment mode. The nanogenerator with BaTiO3 nanofibers aligned vertically in the PDMS matrix sheet achieved high piezoelectric performance of an output power of 0.1841 μW with maximum voltage of 2.67 V and current of 261.40 nA under a low mechanical stress of 0.002 MPa, in addition to a high dielectric constant of 40.23 at 100 Hz. The harvested energy could thus power a commercial LED directly or be stored into capacitors after rectification.